2012
DOI: 10.1371/journal.pone.0034351
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptides for the Detection of Paroxysmal Atrial Fibrillation in Patients with Cerebral Ischemia – the Find-AF Study

Abstract: Background and PurposeDiagnosis of paroxysmal atrial fibrillation (AF) can be challenging, but it is highly relevant in patients presenting with sinus rhythm and acute cerebral ischemia. We aimed to evaluate prospectively whether natriuretic peptide levels and kinetics identify patients with paroxysmal AF.MethodsPatients with acute cerebral ischemia were included into the prospective observational Find-AF study. N-terminal pro brain-type natriuretic peptide (NT-proBNP), brain-type natriuretic peptide (BNP) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 23 publications
1
49
0
1
Order By: Relevance
“…The exact cut-off values of 265.5 pg/mL for stroke of known aetiology and 912.0 pg/mL for cryptogenic stroke had high sensitivity and specificity for the diagnosis of paroxysmal AF in patients after stroke [20]. The same diagnostic utility for the detection of paroxysmal AF was confirmed for BNP in patients with cerebral ischaemia [21].…”
Section: Paroxysmalmentioning
confidence: 69%
“…The exact cut-off values of 265.5 pg/mL for stroke of known aetiology and 912.0 pg/mL for cryptogenic stroke had high sensitivity and specificity for the diagnosis of paroxysmal AF in patients after stroke [20]. The same diagnostic utility for the detection of paroxysmal AF was confirmed for BNP in patients with cerebral ischaemia [21].…”
Section: Paroxysmalmentioning
confidence: 69%
“…This ability could be attributed to higher levels of natriuretic peptides in patients with asymptomatic myocardial ischemia15, 16 and paroxysmal atrial fibrillation,17, 18 which could predispose to both MI and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the incidences of outcomes differ between patients with HF8 and patients with a recent ACS9 in a stable phase, it is less established how natriuretic peptides are associated with cardiovascular outcomes, especially subsequent MI and stroke, in the latter population 3, 10, 11, 12, 13, 14. Concentrations of natriuretic peptides may be affected by both asymptomatic myocardial ischemia15, 16 and atrial fibrillation,17, 18 which could make BNP and NT‐proBNP relevant as predictors of MI and stroke. However, trials investigating patients at high risk of atherosclerotic events have found conflicting results regarding both the predictive ability of natriuretic peptides and cardiovascular outcomes—including MI and stroke—as well as the predictive strength of BNP versus NT‐proBNP 19, 20, 21, 22…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been suggested such as BNP level at admission, PAC number, and clinic-radiological scores (e.g. STAF score) [6,20,22,23,24,25,26]. The first-hour risk score in our experience does not appear efficient enough to be included in relevant parameters.…”
Section: Discussionmentioning
confidence: 83%